Correlation of specific coordination by young female volleyball players and performance level of technical elements in volleyball - Tamara Karalić; Adriana Ljubojević; Nikolina Gerdijan; Željko Vukić (University of Banja Luka, Faculty of physical education and sport, 2016)
In a study with transversal character participated 40 female volleyball players, selected by clearly defined critiques. The tests that were conducted are from the domain of specific volleyball coordination (predictors) and the precision of playing a ball with ''bump'' (criteria). The aim is to examine the relationship of predictors on the criterion variables and on that way create a precondition for predicting the level of precision of the female volleyball players. The female volleyball players have shown that they coordinating skills are statistically significant at the test shooting horizontal target with ''bump'' (ČEHOR). In the test shooting vertical target with ''bump'' (ČEVER) they showed up two types of coordination, coordination in space and coordination by the volleyball net, while in the third test, shooting horizontal target with ''bump'' in position 2 (ČEPOZ2), as significant have shown coordination by the volleyball net and one-handed juggling ball through the hoop. The importance and complexity of coordination in this and similar transversal research is evident, so the conclusion is that there is an relationship specific coordinative abilities with the correct performance of volleyball techniques and that latent factors, who have determined the coordinating ability of the female volleyball players can act independently, but also depend on each other. Without a doubt, without a well coordinated volleyball player, we can not expect efficient performance of the set technical-tactical structures in the volleyball game